Cerebroplacental ratio assessment in early labor in uncomplicated term pregnancy and prediction of adverse perinatal outcome: prospective multicenter study. (4th March 2019) - Dall'Asta, A.; Ghi, T.; Rizzo, G.; Cancemi, A.; Aloisio, F.; Arduini, D.; Pedrazzi, G.; Figueras, F.; Frusca, T.
Abstract : Objective: It has been suggested that the use of Doppler ultrasound in term pregnancies with normal‐sized fetuses is able to identify those at high risk of subclinical placental function impairment. The objective of this study was to evaluate the relationship between cerebroplacental ratio (CPR) measured in early labor and perinatal and delivery outcomes in a cohort of uncomplicated singleton term pregnancies. Methods: This was a prospective multicenter observational study conducted at three tertiary centers between January 2016 and July 2017. Low‐risk term pregnancies, defined by the absence of maternal morbidity or pregnancy complication, accompanied by normal ultrasound and clinical screening of fetal growth in the third trimester, with spontaneous onset of labor were included. Umbilical artery (UA) and fetal middle cerebral artery (MCA) Doppler was assessed on admission for early labor. All measurements were performed in between uterine contractions and according to international standards. CPR was computed by dividing MCA pulsatility index by UA pulsatility index and converted into multiples of the median (MoM) in order to adjust for gestational age. Doctors and midwives involved in the clinical management of the women were blinded to the results of the Doppler evaluation. Mode of delivery and perinatal outcome were compared between pregnancies with reduced CPR MoM, defined as CPR MoM within the lowest decile of the study population, and those with normal CPR MoM. Receiver–operating characteristics curve analysis was used to assess the predictive performance of CPR for obstetric intervention due to fetal distress and composite adverse perinatal outcome. Results: Overall, 562 women were included. The rate of obstetric intervention for suspected fetal distress in labor was more than three times higher among cases with reduced CPR MoM compared to those with normal CPR MoM (9/54 (16.7%) vs 28/508 (5.5%); P  = 0.004). Furthermore, a significantly higher rate of composite adverse perinatal outcome was found in fetuses with CPR MoM < 10 th percentile compared to those with CPR MoM ≥ 10 th percentile (6/54 (11.1%) vs 19/508 (3.7%); P  = 0.012). CPR had low sensitivity and low positive predictive value for prediction of obstetric intervention due to fetal distress (24.3% and 18.0%, respectively) and composite adverse perinatal outcome (24.0% and 11.1%, respectively). Conclusions: Data on a wide cohort of low‐risk term pregnancies in early labor showed that, while reduced CPR is associated with a higher risk of obstetric intervention due to fetal distress and composite adverse perinatal outcome, it is a poor predictor of adverse perinatal outcome. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.